2022
DOI: 10.1371/journal.pone.0273251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiac rehabilitation on elderly patients with Chronic heart failure: A meta-analysis and systematic review

Abstract: Aims The purpose of this study was to investigate the effects of cardiac rehabilitation (CR) on elderly patients with Chronic heart failure (CHF) by literature search and meta-analysis. Methods We conducted an electronic search on PubMed, Cochrane Library, Embase, CNKI, Wanfang, and VIP database platforms. The search period was from the establishment of the database to November 2021 for randomized controlled studies (RCTs) related to the effects of CR on elderly patients with CHF. The RevMan 5.4 was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A systematic review of randomized trials of cardiac rehabilitation in older patients with HF demonstrated that this intervention improved 6-min walk distance and decreased hospitalization, with odds ratio (95% CI) 0.32 (0.21–0.49). 19 Another systematic review confirmed that exercise-based cardiac rehabilitation decreases the risk of HF hospitalization. 20 In this systematic review, there were 33 trials that included mortality as an endpoint (666 deaths in 5441 participants), but almost all (99%) were from Europe and North America.…”
Section: Discussionmentioning
confidence: 94%
“…A systematic review of randomized trials of cardiac rehabilitation in older patients with HF demonstrated that this intervention improved 6-min walk distance and decreased hospitalization, with odds ratio (95% CI) 0.32 (0.21–0.49). 19 Another systematic review confirmed that exercise-based cardiac rehabilitation decreases the risk of HF hospitalization. 20 In this systematic review, there were 33 trials that included mortality as an endpoint (666 deaths in 5441 participants), but almost all (99%) were from Europe and North America.…”
Section: Discussionmentioning
confidence: 94%
“…There is, however, robust post-translational evidence for CHF. Generic cardiac and, more specifically, CHF rehabilitation are established in evidence, clinically translated by utilising multidisciplinary care to support improved outcomes [7][8][9], including in the elderly [10]. Care, with similar foundations as cardiac rehabilitation, is routinely advocated in clinical guidelines as a translational tool to enhance multidisciplinary care, following gold-standard evidence in trials and clinical translation [11].…”
Section: Introductionmentioning
confidence: 99%